2020
DOI: 10.1007/s00442-020-04678-w
|View full text |Cite
|
Sign up to set email alerts
|

Bitter fruits of hard labour: diet metabarcoding and telemetry reveal that urban songbirds travel further for lower-quality food

Abstract: Rapidly increasing urbanisation requires mitigation against associated losses of biodiversity and species abundance. In urban-breeding birds, altered food availability for nestlings is thought to reduce reproductive success compared to forest populations. To compensate for shortages of preferred foods, urban parents could increase their search effort for optimal diets or provision other foods. Here, we used telemetry and faecal metabarcoding on blue tits from one urban and one forest populations to compare par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 72 publications
3
50
0
Order By: Relevance
“…When compared to more natural areas, urban environments often harbour a reduced abundance of arthropods (Jones & Leather 2012, New 2015, Fenoglio et al 2020, which may also be of lower quality (e.g., lower carotenoid content in caterpillars at urban versus rural sites; Isaksson & Andersson 2007) and have smaller body size (Merckx et al 2018), resulting in a relative scarcity of high-quality food sources (e.g., lepidopteran larvae; Narango et al 2018, Seress et al 2018, 2020, Jarrett et al 2020 for urban insectivorous birds. On the other hand, cities offer large amounts of low-quality, easily accessible anthropogenic food which is readily consumed by birds (Robb et al 2008).…”
mentioning
confidence: 99%
“…When compared to more natural areas, urban environments often harbour a reduced abundance of arthropods (Jones & Leather 2012, New 2015, Fenoglio et al 2020, which may also be of lower quality (e.g., lower carotenoid content in caterpillars at urban versus rural sites; Isaksson & Andersson 2007) and have smaller body size (Merckx et al 2018), resulting in a relative scarcity of high-quality food sources (e.g., lepidopteran larvae; Narango et al 2018, Seress et al 2018, 2020, Jarrett et al 2020 for urban insectivorous birds. On the other hand, cities offer large amounts of low-quality, easily accessible anthropogenic food which is readily consumed by birds (Robb et al 2008).…”
mentioning
confidence: 99%
“…Four non-mutually exclusive scenarios are possible. First, spatial heterogeneity (habitat fragmentation), lower food availability or human disturbance in the urban environment may decrease coordinated behaviours because parents may need to forage in different locations 24 or further away from the nest 57 . Empirical evidence in zebra finches Taeniopygia guttata showed that parents foraging independently from each other at different foraging areas decreased synchrony of nest visits 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Urban areas, such as our suburban site, may thus induce parents to forage independently from each other more often, resulting in lower coordination of their nest visits. A recent radio-tracking study on blue tits Cyanistes caeruleus showed differences in foraging behaviour between populations at an urban and rural site in that provisioning trips occur on average further from the nest for parents nesting in an urban site compared to a forest site 57 . However, to the best of our knowledge, it is not known whether urban environments also affect other aspect of the foraging behaviour, such as the number of foraging locations or the coordination between the parents (whether parents forage together or independently from each other).Further telemetry studies with both parents tracked simultaneously are necessary to shed lights on space use and pair coordination of foraging parents in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Blue tit chicks typically fledge at 18 days of age and, in our populations, lay an average of nine eggs. Both clutch size and fledging success are usually higher in the forest than in the city sites ( Pollock et al 2017 ; Jarrett et al 2020 ). Nestbox temperature does not differ between our urban and forest sites (Dominoni et al, in review).…”
Section: Methodsmentioning
confidence: 99%